2014
DOI: 10.1148/radiol.13131810
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy-induced Focal Hepatopathy in Patients with Gastrointestinal Malignancy: Gadoxetic Acid–enhanced and Diffusion-weighted MR Imaging with Clinical-Pathologic Correlation

Abstract: CIFH should be considered a mimicker of metastasis in patients with gastrointestinal malignancy during chemotherapy. CIFH can be differentiated from metastasis on the basis of gadoxetic acid-enhanced MR and DW imaging findings; an ill-defined margin on HBP images was especially characteristic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 30 publications
0
36
0
Order By: Relevance
“…It has been proposed that increased spleen size may serve as a biomarker of OBC-induced SOS (12), and reticular signal intensity at hepatobiliary phase of gadoxetic acid-enhanced MR imaging and superparamagnetic iron oxide-enhanced MR imaging can accurately help predict SOS presence (15)(16)(17). Oxaliplatin-induced SOS was also reported to manifest as focal liver lesions closely resembling metastasis on CT or MR images (26)(27)(28). However, to our knowledge, no previous studies have reported on the correlation of postchemotherapy parenchymal changes of liver on CT scans with clinical factors.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that increased spleen size may serve as a biomarker of OBC-induced SOS (12), and reticular signal intensity at hepatobiliary phase of gadoxetic acid-enhanced MR imaging and superparamagnetic iron oxide-enhanced MR imaging can accurately help predict SOS presence (15)(16)(17). Oxaliplatin-induced SOS was also reported to manifest as focal liver lesions closely resembling metastasis on CT or MR images (26)(27)(28). However, to our knowledge, no previous studies have reported on the correlation of postchemotherapy parenchymal changes of liver on CT scans with clinical factors.…”
Section: Discussionmentioning
confidence: 99%
“…Although there were no statistically significant differences in the diagnostic performance of MRI between the chemonaive group and the chemotherapy group, the slightly lower diagnostic performance of gadoxetic acid-enhanced MRI in the chemotherapy group may be mainly attributed to the larger number of smaller (≤1 cm) lesions in the chemotherapy group (n=27 in the chemotherapy group vs. n=11 in the chemonaive group). In a recent study by Han et al [31], chemotherapy-associated hepatic lesions such as sinusoidal dilatation, peliosis and nodular regenerative hyperplasia were referred to as chemotherapy-induced focal hepatopathy, in which their radiologic appearance mimicked hepatic metastasis. However, sinusoidal dilatation, peliosis and nodular regenerative hyperplasia mimicking hepatic metastasis were not confirmed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies has demonstrated MRI techniques, such as SPIO-enhanced T2-weighted GRE images and gadoxetic acid-enhanced magnetic resonance imaging identified HSOS in the patients of colorectal cancers who had received oxaliplatin-based chemotherapy141617. Given the difference in the cause of HSOS, radiological features of oxaliplatin-induced HSOS might be hardly extrapolated to PAs-induced HSOS.…”
Section: Discussionmentioning
confidence: 99%
“…In the patients who had undergone oxaliplatin-based chemotherapy, the most common feature of enhanced CT was heterogeneous hypoattenuation of the hepatic parenchyma on CT or MRI scan14161721. In HSOS patients (12 cases) after HSCT, periportal edema, ascites, and a narrow right hepatic vein were common findings of CT; while, heterogeneous hypoattenuation and patchy enhancement were not observed22.…”
Section: Discussionmentioning
confidence: 99%